APeC Automated People Counting through video - Adriano, Georgino P. (2005)
vAPeC is a video monitoring system that is used to count the number of people passing through a monitored area. This system accepts as input a video file and outputs a bidirectional count of the human traffic caught on the video. It is composed of two modules: the People Detection module and the People Counting module. A single camera is placed directly above a door to get a clear top view of human traffic. Each frame taken from the video recorded by the camera is used as input to the people detection module. People Detection takes care of distinguishing the people from the rest of the objects in the frame by the dark color of the hair. The people detected in every frame are marked frame are marked as blobs. In the People Counting module, every blob's movement is tracked through three monitored zones. When it passes these zones in a specific order, a count is made. Detection of the blob motion is also tracked to determine if the person is entering or leaving the monitored area. During experimentation, the system was able to successfully detect 93% of the people passing and did not have any false positives.